2022
DOI: 10.1108/sef-05-2021-0186
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of economic policy uncertainty on Bitcoin’s hedging power

Abstract: Purpose Even though Bitcoin has been often labelled as a safe haven asset class in the literature, the influence of economic policy uncertainty (EPU) on the diversifying opportunities offered by Bitcoin in relation to other assets needs to be investigated. This paper aims to investigate how the EPU affects diversification of commodity, conventional, Islamic and sustainable equity returns in relation to its impact on Bitcoin returns. Design/methodology/approach The authors use advanced time-series econometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Bitcoin's encryption algorithm guarantees security. Still, the algorithm then directly limits the total number of issues to 21 million, which results in Bitcoin having a natural scarcity, just like gold [10]. Moreover, governments do not issue digital currencies like Bitcoin and are not backed by credit, and virtual currencies like Bitcoin are decentralized, which leads to three problems.…”
Section: Bitcoinmentioning
confidence: 99%
“…Bitcoin's encryption algorithm guarantees security. Still, the algorithm then directly limits the total number of issues to 21 million, which results in Bitcoin having a natural scarcity, just like gold [10]. Moreover, governments do not issue digital currencies like Bitcoin and are not backed by credit, and virtual currencies like Bitcoin are decentralized, which leads to three problems.…”
Section: Bitcoinmentioning
confidence: 99%
“…The study of Md Hakim Ali et al (2022) shows that EPU is remarkably important in explaining the average portfolio returns of Bitcoin, suggesting that this indicator can be perceived as a decent explanatory factor for portfolio diversification. Also, Jessica Paule-Vianez et al (2020) indicated that their results provide useful information to investors by allowing Bitcoin to be considered as a tool to protect savings in times of economic uncertainty and to diversify portfolios.…”
Section: Introductionmentioning
confidence: 99%
“…Given their exceptional return potential and unpredictable sharp price drops (Shu & Zhu, 2020) during periods of extreme price increases (Cagli, 2019; Hakim das Neves, 2020; Makarov & Schoar, 2020), they have attracted considerable interest in financial circles as an alternative to traditional investment instruments. Schinckus et al (2021) suggest that anonymous cryptocurrencies are very good assets in terms of diversification, while Ali et al (2023) state that Bitcoin emerged as an alternative safe asset in 2008. Bitcoin, Ethereum, Tether, Ripple, and Litecoin are among the cryptocurrencies with the highest market values.…”
Section: Introductionmentioning
confidence: 99%